Penerapan metode cost plus pricing dalam keputusan penentuan harga jual pada pabrik mie rumahan Aneke Emor Desa Tumaratas - Memah, Natasya Grasilia; Saerang, David P. E.; Mintalangi, Syermi S. E. (Yayasan Widyantara Nawasena Raharja, 2025)
In the cutthroat world of competitive food manufacturing, SMEs like home-based noodle factories find it tough to set competitive and profitable selling prices, especially when raw material costs are volatile. This study adopts the cost plus pricing method to determine the selling price of noodles produced by the Aneke Emor home-based noodle factory.The research method utilized is qualitative, with data collected through interviews and a thorough analysis of the factory's production data. The Full Costing approach shows a cost of goods sold (COGS) of IDR10,426 per kilogram, compared to the factory's traditional calculation method of IDR10,037 per kilogram. Adding a 10% profit margin raises the selling price to Rp 11,469 per kilogram, significantly above the previous price of IDR11,000. It is clear that the Cost-Plus Pricing Method enhances profitability and business competitiveness. SMEs should apply this method to maximize profits and support the long-term sustainability of their business.